Limitations of the Cancer of the Prostate Risk Assessment (CAPRA) Prognostic Tool for Prediction of Metastases and Prostate Cancer-specific Mortality in Patients Treated With External Beam Radiation Therapy. (April 2016) - Vainshtein, Jeffrey M.; Schipper, Matthew; Vance, Sean; Feng, Felix Y.; Olson, Karin B.; Hamstra, Daniel A.
Abstract : Objectives: To assess the performance of the Cancer of the Prostate Risk Assessment (CAPRA) prognostic tool for freedom-from-metastases (FFM) and cause-specific survival (CSS) in patients with localized prostate cancer treated with definitive external beam radiotherapy (EBRT), and to determine whether the performance of CAPRA is influenced by androgen deprivation therapy (ADT) use or the presence of Gleason pattern 5 (GP-5). Materials and Methods: A total of 612 patients from a prospective database of 718 patients treated with dose-escalated EBRT from 1998 to 2008 who met CAPRA scoring criteria were included in the study. Performance of CAPRA and association of CAPRA score, GP-5 and short-term or long-term ADT use (STAD or LTAD, respectively) with FFM and CSS were evaluated using Cox models. The impact of ADT use on accuracy of the CAPRA-based CaPSURE model for CSS was assessed. The discriminatory ability of the CAPRA model and modified models incorporating GP-5 and ADT use were compared using the C -index. Results: Increasing CAPRA score correlated with worse FFM and CSS, and was prognostic for FFM and CSS for the overall cohort. CAPRA showed poorer discrimination for FFM and CSS in patients treated with EBRT+LTAD than those who received EBRT alone or EBRT+STAD. The addition of GP-5 and ADT use to CAPRA score increased the predictive accuracy of the CAPRA model for both FFM ( C -index 0.809 vs. 0.779, P <0.001) and CSS ( C -index 0.864 vs. 0.796, P =0.003). Conclusions: The CAPRA score should be modified to incorporate GP-5 and ADT use for risk adjustment and risk prediction in prostate cancer patients who receive EBRT. Abstract : Supplemental Digital Content is available in the text.